The efficacy profiles of concurrent chemoradiotherapy with intensity-modulated radiotherapy followed by durvalumab in patients with unresectable stage III non–small cell lung cancer: A multicenter retrospective cohort study. (November 2022) - Takeda, Yuichiro; Kusaba, Yusaku; Tsukita, Yoko; Uemura, Yukari; Miyauchi, Eisaku; Yamamoto, Takaya; Mayahara, Hiroshi; Hata, Akito; Nakayama, Hidetsugu; Tanaka, Satoshi; Uchida, Junji; Usui, Kazuhiro; et al.
Highlights: The tri-modalities of chemoradiotherapy (CRT) with IMRT and durvalumab were evaluated. We have reported the efficacy and safety of tri-modalities through real-world data. A better response to CRT and increasing radiation dose are related to long PFS. Durvalumab therapy duration was linked to survival in patients. Abstract: Purpose: Intensity-modulated radiotherapy (IMRT) is currently used more commonly than 3-dimensional conformal radiation for definitive thoracic radiation. We examined the efficacy profiles of concurrent chemoradiotherapy (CCRT) with IMRT after durvalumab became clinically available. Methods: We reviewed the clinical records of patients with stage III non-small cell lung cancer (NSCLC) treated with CCRT and IMRT at seven centers in Japan and investigated relapse and survival from May 2018 to December 2019. The primary endpoint of this report was progression-free survival (PFS). Results: Among 107 patients enrolled in the study, 87 were sequentially administered durvalumab. From CCRT commencement, patients were followed up for a median period of 29.7 months. The median PFS at the end of the CCRT was 20.7 months. Among the 87 patients, 58 experienced disease relapses, of whom 36 (62.1 %) had distant metastases. Multivariate Cox regression analysis revealed that a favorable response to CCRT, a radiation dose ≥ 62 Gy, and stage IIIA NSCLC were associated with prolonged PFS (all P = 0.04). Multivariate logistic regression by landmark analysis revealed that mortality risk factors were durvalumab treatment duration ≤ 11.7 months, a lower maximum grade of immune-related adverse events, FEV1  < 2805 mL, and radiation dose < 62 Gy (P = 0.01, 0.01, 0.03, and 0.04, respectively). Conclusions: In patients with NSCLC receiving CCRT using IMRT, long PFS was associated with a better response to CCRT, stage IIIA NSCLC, and an increased radiation dose. The duration of durvalumab consolidation also played an essential role in the survival of patients receiving CCRT with IMRT. (250 words)